IMPLEMENTASI METODE MIND MAPPING PADA PEMBELAJARAN SEJARAH KEBUDAYAAN ISLAM DALAM MENINGKATKAN EFEKTIVITAS BELAJAR SISWA KELAS VII DI MTs YKUI MASKUMAMBANG GRESIK - Ikrom, Abdu Dzil Jalali Wal (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
The research was motivated by educational problems, which is the weak interest and motivation of students in accepting Islamic Cultural History subjects. This fact affects so that the low grades achieved in Islamic Cultural History subjects. Given the importance of SKI subjects, these subjects should be accepted by students effectively. For this reason, the problems above must be anticipated as much as possible. The formulation of the problem of this thesis, First: How is Islamic Cultural History learning at MTs YKUI Maskumambang Gresik? Second: How is the implementation of the Mind Mapping method in SKI learning in increasing the learning effectiveness of class VII students at MTs YKUI Maskumambang Gresik? Third: What are the supporting and inhibiting factors in the implementation of the Mind Mapping method in class VII SKI learning at MTs YKUI Maskumambang Gresik? This type of research is a field research that collects primary data through interviews with the principal, teachers, and students of MTs YKUI Maskumambang. Besides, secondary data was used from literature and documents of MTs YKUI Maskumambang. After all the data collected were analyzed qualitatively, in descriptive form. From the results of the study it can be concluded that: The implementation of the Mind Mapping Method in Islamic Cultural History Learning in Improving the Learning Effectiveness of Class VII Students at MTs YKUI Maskumambang Gresik has been applied in 3 stages. The first stage is the planning stage by making a learning implementation plan (RPP). The second stage, namely the implementation stage, is the core activity in making mind mapping, either individually or in groups. The third stage, is the evaluation of learning by assessing the results on students' cognitive (knowledge) through doing practice questions. From the results of the study found that there was an increase in the learning effectiveness of class VII MTS YKUI Maskumambang Gresik students when the mind mapping method was applied.